A novel large stepping-stroke actuator based on the bridge-type mechanism with asymmetric stiffness. (1st November 2022) - Wang, Fujun; Zhao, Xiaolu; Huo, Zhichen; Shi, Beichao; Tian, Yanling; Zhang, Dawei
Abstract: This paper presents the design, analysis, and experiments of a novel stick–slip actuator with large working stroke and high resolution based on parasitic motion. To meet the requirement on large stepping-stroke in the fields of nanofabrication and nano-characterization, the bridge-type mechanism with asymmetric stiffness which changes the distribution of piezoelectric actuator elongation at two input points is proposed. A chain-based compliance matrix model is established for the static performance characterization and parameter optimization of the dual-input closed-loop compliant mechanism, and the performance is further studied by finite element method. The prototype of the proposed actuator is manufactured and experimental tests are conducted to investigate its characteristics. The results indicate that the maximum motion speed is 23.53 mm/s with the driving frequency of 350 Hz. The stepping-stroke is 102 μm, and the resolution is measured to be 12 nm. It is confirmed that the proposed actuator is feasible to enlarge the stepping-stroke and work stably.